Rehabilitation in locked-in-syndrome – a case study - Grabowska, Anna; Zgórzyńska, Justyna; Wesołowska, Monika; Wójcicki, Marcin; Nicpoń-Nożewska, Klara; Podhorecka, Marta; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Introduction: The locked-in syndrome is a neurological condition which occurs most often as a result of brainstem stroke, characterized by the presence of sustained eye opening, aphonia or severe hypophonia, quadriplegia or quadriparesis, preserved cognitive functioning, and a primary and elementary code of communication using vertical eye movements or blinking. This illness leads to complete physical disability of the person, accompanied with fully retained mental capability. Case study: The goal of the hereby work is to present a description of a case of a person with the locked-in syndrome, caused by ischemic stroke of the pons and left cerebellar hemisphere. The prognosis of improvement in LIS is bad. The patient has to adapt to the new, difficult situation that will probably accompany him for whole life. The article presents the therapeutic process from the onset through physical rehabilitation, speech therapy and psychological therapy until return home. The process requires patience from the patient and therapists and family members. Conclusion: Research in this area is supposed to help in planning of cooperation the entire medical team of doctors, nurses, physiotherapists, social workers, speech therapists and neuropsychologists. Interdisciplinary proceedings can greatly help to achieve even a minimal degree of independence and autonomy.